Experience of anganwadi workers running VCNC under ‘Misssion Balam Sukham’ in a tribal area of Gujarat, India - Zalavadiya, Dhara I.; Kuriya, Suraj I.; Mazumdar, Vihang S.; Patel, Sangita V. (International Journal Of Community Medicine And Public Health, 2017)
Background: State Government has started a programme “Mission Balam Sukham” to combat the malnutrition with 3 tier approach including Village Child Nutrition Center (VCNC), Child Malnutrition Treatment Center (CMTC) and Nutrition Rehabilitation Center (NRC). Present study was conducted with the objectives to compare the availability of articles present at anganwadies and VCNCs and to know the experience of anganwadi workers running VCNC. Methods: Ten VCNCs from Naswadi block were selected by systemic random sampling and compared with 10 anganwadies as control group from nearby block Sankheda to check the availability of necessary articles. Ten anganwadi workers who ran the VCNCs for 1 month were interviewed about their experience of running VCNC. Results: There were not major differences in availability of articles like weight machine, MUAC tap, IMNCI (Integrated management of neonatal and childhood illnesses) chart, utensils for cooking, soap and water supply, common medicines and food articles between control anganwadies and VCNCs. Some of the articles like referral slips and thermometer were lacking at control anganwadies as well as VCNCs. Anganwadi workers (AWW) did not get enough medicines and functioning weighing scales and proper training before starting the VCNCs. Conclusions: VCNC needs to supply proper medicine stocks, functional weighing scale and other necessary articles to make the programme successful. AWWs also need the proper training to identify and treat the malnutrition at anganwadi centres.